Little women - DiNovi, Denise; Armstrong, Gillian; Columbia Pictures (Firm); DiNovi Pictures (Firm) (Culver City, Calif. : Columbia TriStar Home Video, 2000)
Story about the March family of four daughters and a strong mother who, because her husband is away serving in the Army during the Civil War, must raise her'little women' on her own. The daughters include: spirited Jo who longs for a career as a writer; beautiful and conservative older sister Meg; fragile Beth; and the romantic Amy. Through the years, as they become women, the sisters share their most cherished and painful moments of self-discovery as their mother's pride and strength guide them through questions of independence, romance and virtue
Play using computer software. Best play in VLC Media Player.
Based on the novel by Louisa May Alcott
Cast: Winona Ryder, Gabriel Byrne, Trini Alvarado, Samantha Mathis, Kirsten Dunst, Claire Danes, Christian Bale, Eric Stoltz, John Neville, Mary Wickes, Susan Sarandon
DVD Format
Subtitle available in English
Keywords: Young women -- Massachusetts -- Drama; Mothers and daughters -- Massachusetts -- Drama; Families -- Massachusetts -- Drama